Storage of Decapsulated Artemia (Brine Shrimp) - Jason Broach; Cortney L. Ohs; Isaac Lee (EDIS)
Artemia (brine shrimp) are good food for larval fish, but they have to be removed from their shells before many species can eat them. The process can be time- and labor-intensive, especially since it is often performed every day. Fortunately, this 3-page fact sheet written by Jason Broach, Cortney Ohs, and Isaac Lee and published by the UF/IFAS School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences describes a method for storing a 7-day supply of the brine shrimp that will allow the task to be done just once a week. https://edis.ifas.ufl.edu/fa203